The Online/Offline Distinction Will Dissolve. - Hart, Tiernan (Flusser Studies, 2024)
This article explores the dissolution of the online/offline distinction and the impact of information technologies on space and time. It introduces the concept of hybrid space, where physical reality and virtual significance intertwine. The role of digital objects and their relation to spatiality is discussed, as well as the reorganization of space and the concept of diachronic time through Flusser's technical image. The text argues that apparatuses and people are mutually dependent, shaping each other's intentions and actions. It also highlights the temporal aspects of technical images and their role in externalizing culture and memory. The circulation and significance of technical images are emphasized, drawing parallels between their circular temporality and the circulation of capital. The text also discusses the role of information in mediating between machines and workers in cognitive capitalism, but acknowledges the continued exploitation and suffering in industrial capitalism, particularly for marginalized groups.